Chemical constituents and antitumor activity from Paris polyphylla Smith var. yunnanensis. Issue 6 (19th March 2017) - Jing, Songsong; Wang, Ying; Li, Xia; Man, Shuli; Gao, Wenyuan
Abstract: Eleven compounds were isolated from the rhizomes of Paris polyphylla Smith var . yunnanensis . Their structures were elucidated on the basis of rigorous 1D and 2D NMR experiments as well as comparison with the literature data. To the best of our knowledge, compound1 was only predicted by UPLC/Q-TOF MS E and the NMR spectroscopic data was given for the first time. The cytotoxic activities of all compounds on mouse B16 cells were evaluated. Among the tested molecules, compounds6 –9 showed strong cytotoxicities, while compound1 did not show significant effect. Abstract :